Vin Garbutt performs at the National Folk Festival Saturday night concert at the fourteenth National Folk Festival in Alice Springs in the Top End Folk Club collection. - Garbutt, Vin; Top End Folk Club.; National Folk Festival 1980: Alice Springs, N.T.) (1980)
Folkloric recording.
The ballad of Hugh Reynolds / Vin Garbutt -- The land of three rivers / Vin Garbutt -- Brides favourite/The flowing tide / Vin Garbutt -- Tunes / Vin Garbutt -- The ring of iron / Vin Garbutt -- The woolen and linen song / Vin Garbutt -- Parkin Raine, the fiddler of Teesdale / Vin Garbutt.
Recorded on 5 April 1980 in Alice Springs, N.T.
Digital master available
Summary not yet available.
Keywords: Folk songs, English; Folk festivals -- Northern Territory -- Alice Springs